Factors associated with concordance of mother-child (6–23 months) dietary diversity in Sub-Saharan Africa - Meklit Melaku Bezie; Hiwot Altaye Asebe; Angwach Abrham Asnake; Bezawit Melak Fente; Zufan Alamrie Asmare; Alemayehu Kasu Gebrehana; Mamaru Melkam; Beminate Lemma Seifu; Sintayehu Simie Tsega; Yohannes Mekuria Negussie (PLoS ONE, 2025)
Background Inadequate dietary diversity is a major contributor to undernutrition, and compromises the health of both mothers and children. Available evidence demonstrates a significant association between maternal and child dietary diversity. However, there is limited evidence about the factors influencing the concordance of mother-child dietary diversity in Sub-Saharan Africa (SSA). Therefore, we investigated the factors associated with the concordance of mother-child dietary diversity in SSA. Methods A community-based cross-sectional study was conducted based on the recent Demographic and Health Surveys (DHS) data of eight Sub-Saharan African countries. A total weighted sample of 29,138 mother-child pairs within the five years preceding the survey was included. A mixed-effect binary logistic regression model was employed to identify factors associated with concordance between mother-child dietary diversity. Variable with p-value < 0.2 in the bivariable mixed-effect binary logistic regression analysis was considered for the multivariable analysis. In the multivariable mixed-effect binary logistic regression analysis, the Adjusted Odds Ratios (AOR) with 95% Confidence Intervals (CI) were reported. The percentage of agreement between mothers and children with minimum dietary diversity was assessed using kappa statistics. Results The concordance of dietary diversity between mother-child pairs in SSA was 74.48% (95% CI: 73.98, 74.98). A higher likelihood of mother-child dietary diversity concordance was significantly associated with mothers who had a primary level of education (AOR = 1.40, 95% CI: 1.31, 1.53) and those who were divorced or widowed (AOR = 1.54, 95% CI: 1.29, 1.84). Conversely, lower odds of concordance were observed among mothers with higher education (AOR = 0.75, 95% CI: 0.66, 0.85), those exposed to media (AOR = 0.78, 95% CI: 0.73, 0.83), and mothers belonging to poorer (AOR = 0.81, 95% CI: 0.74, 0.88), middle-income (AOR = 0.82, 95% CI: 0.75, 0.89), richer (AOR = 0.80, 95% CI: 0.73, 0.88), and richest (AOR = 0.75, 95% CI: 0.67, 0.83) households. Conclusion The findings highlight that the dietary diversity concordance between mother-child pairs in sub-Saharan Africa is moderate at 74.48%. However, the factors influencing concordance suggest socio-economic and educational disparities. Mothers with a primary education level and those who were divorced or widowed had higher concordance with their children’s dietary diversity, indicating their potential prioritization of family dietary habits despite limited resources or support systems. On the other hand, lower concordance among mothers with higher education and those exposed to media suggest that these groups may adopt more individualized dietary practices. Furthermore, households with higher economic status, surprisingly, exhibited lower concordance, which may indicate resource allocation differences within wealthier families or greater dietary autonomy among children. Globally, one-fourth of children aged 6–23 months and two-thirds of women of reproductive age suffer from micronutrient deficiencies, primarily due to inadequate dietary diversity [1–3]. It is estimated that 50–70% of the global disease burden is associated with poor dietary patterns and malnutrition [4]. In Low- and Middle-income Countries (LMICs), where many impoverished and rural households depend on starchy staples due to limited access to diverse foods, only 20% of children meet minimum acceptable dietary standards, exacerbating malnutrition and related health challenges [5,6]. Dietary Diversity (DD) is recognized as a key indicator of a healthy diet, reflecting the variety of food groups consumed within 24 hours [7]. According to the World Health Organization (WHO), DD serves as a proxy for child feeding practices, with consumption from at least four different food groups indicating that the child likely consumed an animal-source food, a fruit or vegetable, and a staple food such as grains, roots, or tubers [8].